Desenvolvimento de novos produtos em startups: proposta de um artefato para a avaliação de nível de maturidade - Kakuta, Susana Maria (Universidade do Vale do Rio dos Sinos, 2023)
With distinct characteristics from traditional companies, startups stand out for their capability to develop innovative products and bring them to market quickly. However, they also face significant challenges, particularly in developing new products. This doctoral dissertation aims to investigate the relevant strategic dimensions in the development of new products in startups and how they manifest themselves in the management of such businesses. These strategies are well delimited in the literature of traditional companies but lack theoretical-empirical deepening in the context of startups. Barczak and Kahn (2012) proposed an assessment instrument with seven strategic dimensions for traditional companies: Strategy, R&D Capability, Commercialization, Process Management, Project Climate, Organizational Culture, and Performance Indicators. These dimensions potentially contribute to developing and inserting new products in the market. Based on Barczak and Kahn's (2012) construct, the research sought to adapt and expand these strategic dimensions to the context of startups. The study used the DSR - Design Science Research methodology, and the results were validated through quantitative questionnaires applied to specialists and startups. Based on conceptual reviews and the incorporation of other authors, conceptual similarities and differences were identified in the strategic dimensions between traditional companies and startups, consolidating new knowledge. Also, it was identified that the dimensions proposed by Barczak and Kahn (2012) can be applied to startups, with adjustments in their description. However, evidence-based PDMA (Product Development & Management Association) certification does not apply to startups. Thus, new evidence was developed based on constructs from other authors, the researcher's experience, and the validation of specialists. In addition, three new specific strategic dimensions for startups were proposed: Interaction in Ecosystems, Digital Insertion, and Financial Capability. Based on these analyses, a set of 10 strategic dimensions relevant to developing new products in startups was consolidated: Strategy, R&D Capability, Commercialization, Process Management, Project Climate, Organizational Culture, Performance Indicators, Digital Insertion, Interaction in Ecosystem, and Financial Capability. Based on this set of 10 dimensions, a digital artifact was developed to diagnose the level of maturity in implementing these management practices in startups. The results of applying this artifact to a set of startups indicated that, on average, these companies do not have evidence of implemented, documented, traceable, and routinely used new product development management practices in all examined strategic dimensions. The most negative performances were in the dimensions of Financial Management, Organizational Culture, and Project Climate, which represents an important organizational challenge since these dimensions directly affect the survival and credibility of startups. On the other hand, the dimensions of R&D Capability and Digital Insertion showed the best performances, reflecting the essential characteristics of startups. The developed digital artifact is available at www.startupacademy.digital/diagnostico-de-maturidade. Therefore, this research offers a means of diagnosis to help startups improve their management practices and increase their chances of success.
Keywords: Inovação; Desenvolvimento de novos produtos; Startups; Maturidade; Gestão; Artefato de avaliação; Boas práticas; Innovation; New product development; Maturity; Management; Assessment tool/artifact; Best practices; ACCNPQ::Ciências Sociais Aplicadas::Administração